Evolution of surface damage of thin film composite (TFC) reverse osmosis (RO) membranes under controlled hygro-mechanical conditions - Abedalkader Alkhouzaam (15842647) (2023)
Limited attention has been given to understanding how failure to the selective layer of reverse osmosis (RO) membranes develops and accumulates during operation; and to integrating this response into membrane fabrication. While the integrity of the selective layer is crucial for the separation process, available studies are limited to simple loading conditions and use failure of the entire membrane at rupture to represent its mechanical integrity. This work aims to investigate the evolution of surface damage to the selective layer under controlled interrupted mechanical tests under dry and wet conditions. AFM, SEM, and contact angle are used to characterize the selective layer integrity. Wet membranes exhibited lower strain at rupture (10.3%) than that of dry membranes (12.3%). However, interrupted tests revealed that the failure of the selective layer occurred at much lower strains than the rupture strain. Stretching and thinning in the TFC layer were observed at strain limits as low as 5%, which developed into localized deformation and cracks at higher strain limits (i.e., 8%). These findings can explain why membranes fail to perform before rupture occurs. By understanding how the selective layer's surface damage evolves during operation, membrane fabrication can be improved to enhance membrane performance and durability.  Other Information Published in: Surfaces and Interfaces License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://doi.org/10.1016/j.surfin.2023.102911